Deliberation and Development : Rethinking the Role of Voice and Collective Action in Unequal Societies - Heller, Patrick; Rao, Vijayendra (Washington, DC: World Bank, 2015)
Deliberation is the process by which a group of people, each with equal voice, can - via a process of discussion and debate - reach an agreement.